Positivisme Sebagai Era Baru Filsafat dan Pengaruhnya Dalam Kajian Sosial Islam - Setiawan, Priatna Agus (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study discusses positivism as one of the important milestones in the history of modern philosophy and its influence on the development of social sciences, especially in the context of Islamic social studies. Positivism, pioneered by Auguste Comte, emphasizes the importance of an empiricism-based scientific approach to understanding reality. This philosophy shifts the paradigm from a metaphysical approach to observing and verifying measurable facts. The influence of positivism in social sciences is seen in the development of systematic and data-oriented research methods. In Islamic social studies, the positivistic approach presents opportunities and challenges. On the one hand, it enriches research methodology by encouraging the use of empirical data. On the other hand, it clashes with Islamic epistemology which integrates revelation and reason as sources of knowledge. This study concludes that the positivistic approach can be critically adopted in Islamic social studies. Combining empirical methods with Islamic normative values ​​is needed to create a more holistic social analysis. Thus, positivism, although limited to the empirical dimension, remains relevant if used wisely within the framework of the Islamic paradigm.